Confined colloidal droplets dry to form circular mazes - Ilaria Beechey-Newman; Natalya Kizilova; Andreas Andersen Hennig; Eirik Grude Flekkøy; Erika Eiser (Proceedings of the National Academy of Sciences, 2025)
During drying, particle-laden sessile droplets will leave so-called coffee-stain rings behind. This phenomenon is well known and well understood (Deegan et al ., Nature 389 , 827–829 (1997). Here, we show that when particle-laden droplets confined in a slit are allowed to evaporate very slowly, they do not deposit coffee rings, but form surprisingly intricate, circular maze-like patterns. We present experiments that illustrate this pattern formation and discuss the factors that determine when such patterns can form. We are not aware of reports of natural examples of the formation of such beautiful patterns under confinement, although it seems likely that they exist.